#### Answer

$-\frac{1}{12}$

#### Work Step by Step

Convert all the fractions to like fractions with the least common denominator of 12. To find the difference of like fractions, subtract the numerators and retain the common denominator.
$1-\frac{1}{2}-\frac{1}{3}-\frac{1}{4}\longrightarrow$ change the denominator of each fraction to 12
$=1-\frac{1\times6}{2\times6}-\frac{1\times4}{3\times4}-\frac{1\times3}{4\times3}\longrightarrow$ simplify
$=1-\frac{6}{12}-\frac{4}{12}-\frac{3}{12}\longrightarrow$ subtract each term working left to right
$=\frac{6}{12}-\frac{4}{12}-\frac{3}{12}$
$=\frac{2}{12}-\frac{3}{12}$
$=-\frac{1}{12}$